2015
DOI: 10.1088/0268-1242/30/9/094018
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth concentration inhomogeneity in GaAsBi bulk and quantum well structures

Abstract: The optical and structural properties of GaAsBi bulk and quantum well (QW) samples grown under various conditions were studied by photoluminescence (PL), high resolution x-ray diffraction (HR-XRD) and transmission electron microscopy (TEM). At 10 K, the 90 nm bulk sample shows two PL peaks at 1.18 and 1.3 eV. The temperature and power dependent PL data suggest that both PL peaks originate from the GaAsBi layer which consists of two regions with different Bi concentrations. The TEM images verify that the Bi con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It has been identified that Bi has a tendency to incorporate inhomogeneously during growth, with recent structural characterisations of the material showing the content of Bi decreasing exponentially after the first 10–25 nm of growth to a near constant level in the remainder of the layer 37,38 . With this in mind, to ensure that emission originates from the homogeneous region of GaAsBi closest to the surface, the sample was selectively excited using a continuous wave Power Technology Inc. diode laser emitting at 3.06 eV, with incident excitation power ranging from 0.33–1494  Wcm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been identified that Bi has a tendency to incorporate inhomogeneously during growth, with recent structural characterisations of the material showing the content of Bi decreasing exponentially after the first 10–25 nm of growth to a near constant level in the remainder of the layer 37,38 . With this in mind, to ensure that emission originates from the homogeneous region of GaAsBi closest to the surface, the sample was selectively excited using a continuous wave Power Technology Inc. diode laser emitting at 3.06 eV, with incident excitation power ranging from 0.33–1494  Wcm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…The inhomogeneous distribution of Bi atoms [241] and the Bi pairs/clusters-related acceptor levels near the VBM [67,221] are the dominant reasons for the spectral broadening in thin-film bismides. In addition, the Bi-induced interface change plays another important role in spectral broadening in the quantum structure.…”
Section: Spectral Broadening In Dilute Bismidesmentioning
confidence: 99%
“…The quality of GaAsBi QW is also dependent on the Bi composition and the growth temperature. For particular growth condition, the flux has to be precisely controlled because a shortage of Bi can result in a surface roughness whereas a Bi excess causes formation of Bi droplet [23,27,37]. All these factors favor lifting the parity restrictions for the 1e→2hh transitions in our dilute bismides.…”
Section: A) Dependence On Excitation Intensitymentioning
confidence: 99%
“…While such losses are a common problem for telecommunication devices, utilization of GaAsBi alloys could benefit laser diodes operating in the 1.3-1.6 µm spectral range with improved operation efficiency and temperature insensitivity [9,12,18]. These and other applications have stimulated extensive recent studies of dilute bismides [19][20][21][22][23][24][25][26][27][28][29][30]. They could make use of high quality GaAs 1-x Bi x /GaAs separate confinement heterostructures [14,31,32] and multiple quantum wells [31,[33][34][35][36][37] in the active regions.…”
Section: Introductionmentioning
confidence: 99%